Study of the yeast cytosolic Hsp70-system in protein homeostasis and life span regulation - Hsp70-mutant yeast cells with the misfolding marker protein guk1-7-GFP, the nucleolar marker Sik1-RFP and nuclear staining with DAPI imaged before, directly after, and during recovery from heat stress - Andersson, Rebecca; Nyström, Thomas (University of Gothenburg, 2020)
Our study aims to answer the question "Which functions of the Hsp70 class of molecular chaperones are essential for yeast to maintain a standard replicative life span?". To answer this question, we utilised the disparate functions of the Hsp70's Ssa1 and 2 and their paralog Ssa4 in a yeast strain that lacks Ssa1/2 but has an ectopically increased production of Ssa4. We have gathered data on the behaviour of several different markers for protein aggregation under different circumstances, as well as data on proteins from other classes of molecular chaperones. The bulk of the data is in the form of multichannel microscopy images from widefield microscopy, with a few sets of western blots of protein extracts.

Fluorescence microscopy of live yeast cells at mid-exponential growth before stress, directly after 30 minutes of heat shock and 40 minutes after heat shock. The yeast is grown in complete synthetic medium lacking uracil with 2 % glucose as carbon source. All strains produce the aggregate marker protein guk1-7-GFP and carry a plasmid expressing SIK1-RFP under the control of the GPD-promoter.
The dataset was collected through fluorescence microscopy.
The image files are provided in Carl Zeiss Image format (.czi).

Vi har systematiskt studerat vilka funktioner hos de cytosoliska molekylära chaperonerna av klassen Hsp70 hos jäst som krävs för att upprätthålla en normal livslängd.

Fluorescensmikroskopi av levande jäst i mitten av den exponentiella tillväxtfasen före, efter 30 minuter värmestress samt 40 minters återhämtning efter stress. Jästen är odlad i syntetiskt medium utan uracil med 2 % glukos som kolkälla. Alla avbildade stammar producerar det felveckade markörproteinet guk1-7-GFP och bär på en plasmid som uttrycker SIK1-RFP under kontroll av en GPD-promotor. Innan avbildning har cellerna färgats med DAPI.
Datasetet hämtades in genom fluorescensmikroskopi.
Bildfilerna är i Carl Zeiss Image-format (.czi).
Studier av det cytosoliska Hsp70-systemet från jäst och dess roll i proteinhomeostas och reglering av livslängd - Hsp70-mutanta jäststammar med det felveckande markörproteinet guk1-7-GFP, nukleolusmarkören Sik1-RFP och kärninfärgning med DAPI avbildad före, direkt efter och i återhämtning från värmestress
Keywords: Molecular Chaperones; Molekylära chaperoner; HSP70 Heat-Shock Proteins; HSP70-värmechockproteiner; Proteostasis Deficiencies; Proteostasbrist; Cell Biology; Cellbiologi; Microbiology; Mikrobiologi; Cell and Molecular Biology; Cell- och molekylärbiologi; Molecular Biology; Molekylärbiologi